The trouble in me - Gantos, Jack (New York : Farrar Straus Giroux, 2015)
"Fourteen-year-old Jack falls under the spell of a delinquent Florida neighbor and gets way more trouble than he bargained for"--
Keywords: Behavior -- Fiction; Juvenile delinquency -- Fiction; Friendship -- Fiction; Moving, Household -- Fiction; Florida -- Fiction; Humorous stories; Juvenile delinquency -- Juvenile fiction; Teenage boys -- Juvenile fiction; Influence (Psychology) -- Juvenile fiction; Self-destructive behavior in adolescence -- Juvenile fiction; Friendship -- Juvenile fiction; Moving, Household -- Juvenile fiction; Miami (Fla.) -- Juvenile fiction; Humorous fiction